Use of Photovoltaics in Microgrid as Energy Source and Control Method Using MATLAB/SIMULINK - Sumaiya Rahman; Hasimah Abdul Rahman (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Microgrid in power system has drawn wide attention due to its significant benefits in terms of sustainable energy system in recent years. This approach is the most economical alternative to conventional energy system which uses Renewable Energy (RE) resources. RE sources ensure pollution free and clean environment by emitting zero CO2. This paper proposes a design of a microgrid system using solar photovoltaics (PV) as the Distributed Energy Resources (DERs) and a controlling method for managing the components of microgrid by using MATLAB/SIMULINK. The results show that microgrid system is promising as alternative to replace the fossil fuel based energy system. Integration of an effective controller can help to manage the loads and resources, resulting in more stable and reliable.